Kualitas Pelayanan Penyediaan Air Bersih Pada Bengkalis Perusahaan Daerah Air Minum (PDAM) Tirta Siak di Kota Pekanbaru - Dewi, Ratna; Kartini, Riska; Mardiah, Ainun (PUBLICNESS: Journal of Public Administration Studies, 2023)
The purpose of this study is to determine the quality of service at the office of the Regional Water Supply Company (PDAM) Tirta Siak Pekanbaru City and what are the inhibiting factors. The theory used is the theory of Zeithaml Parassuraman &; Berry there are five dimensions to measure service quality, namely tangibbles, realbility, responsive, assurance, empathy. This study uses qualitative research with a descriptive approach obtained through interviews, documentation, and observation. There are two population groups and samples in this study, namely 3 employees and 10 customers. The sampling technique used in determining individuals is purposive sampling. The results of this study show that the service quality of PDAM Tirta Siak Kota Pekanbaru is still not running well in accordance with customer satisfaction, only one indicator is assurance that has been running well to its customers. While the tangibbles, reability, responsive, empathy indicators are concluded that they have not been implemented properly. The inhibiting factors that affect the quality of PDAM Tirta Siak Kota Pekanbaru services are lack of human resources, absence of working time SOPs and lack of equitable distribution of routine checks every month to customers' homes.